Magnetic Resonance Imaging-Proton Density Fat Fraction vs. Transient Elastography-Controlled Attenuation Parameter in Diagnosing Non-alcoholic Fatty Liver Disease in Children and Adolescents: A Meta-Analysis of Diagnostic Accuracy - Jia, Shuangzhen; Zhao, Yuzhen; Liu, Jiaqi; Guo, Xu; Chen, Moxian; Zhou, Shaoming; Zhou, Jianli (Frontiers in Pediatrics, 2022)
Background and aim: Nonalcoholic fatty liver disease (NAFLD) has become the most common cause of chronic liver disease in children and adolescents. This study aimed to conduct a meta-analysis to determine the efficacy and accuracy of the MRI-proton density fat fraction (PDFF) and the TE-controlled attenuation parameter (CAP) in evaluating the evaluation of hepatic steatosis discriminated between children and adolescents. Materials and methods: In this study, the PubMed, Cochrane Library, Embase, Medline and Web of Science databases were searched to retrieve articles eligible for this study. The literature included was only from articles on determination of accuracy of MRI-PDFF and TE-CAP to evaluate the grading of steatosis diagnosed in children and adolescents with NAFLD. This study drew the comparison of the sensitivity, specificity, hierarchical summary receiver operating characteristic curves (HSROC) and clinical utility of the MRI-PDFF and the TE-CAP in the classification of steatosis grades 0 vs.1 to 3. Results: A total of eight articles with 874 children and adolescents were included in this study. The MRI-PDFF achieved the diagnostic accuracy for the detection at stage 1, with a summary sensitivity of 0.95 (95% CI, 0.92 to 0.97), a specificity of 0.92 (95% CI, 0.77 to 0.98) and a HSROC of 0.96 (95% CI, 0.94 to 0.98). The TE-CAP achieved the diagnostic accuracy for the detection of steatosis stage ≥S1, with a summary sensitivity of 0.86 (95% CI, 0.70 to 0.94), a specificity of 0.88 (95% CI, 0.71 to 0.96) and a HSROC of 0.94 (95% CI, 0.91 to 0.95). Following a ‘positive’ measurement (over the threshold value) for ≥S1, the corresponding post-test probabilities of the PDFF and the CAP for the presence of steatosis reached 92% and 88%, respectively, at the pretest probability of 50%. If the values were below the mentioned threshold values (‘negative’ results), the post-test probabilities of the PDFF and the CAP took up 5% and 13%, respectively. Conclusion: Therefore, it is evident that both MRI-PDFF and TE-CAP can be used as a highly accurate noninvasive methods for quantification and grading of hepatic steatosis in children and adolescents with NAFLD.